Pengaruh Free Cash Flow, Managerial Ownership, dan Leverage Terhadap Real Earnings Management : Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019 - 2023 - Saputro, Derinto; Taqwa, Salma (Jurnal Nuansa Karya Akuntansi, 2025)
This study examines the effect of Free Cash Flow, Managerial Ownership, and Leverage on Real Earnings Management in manufacturing companies listed on the Indonesia Stock Exchange during the period of 2019 to 2023. The objective of the research is to test the relationships between these variables using a quantitative method and multiple linear regression analysis on secondary data from financial statements. The novelty of this research lies in its focus on the Indonesian manufacturing sector, providing current insights into earnings management practices in a developing market. The results indicate that Free Cash Flow and Managerial Ownership has not significantly influence Real Earnings Management, while Leverage does show a significant negative effect. These findings contribute to the existing literature and offer practical implications for investors and policymakers.